Coworking spaces and makerspaces: Mapping the state of research - Sascha Kraus; Ricarda B. Bouncken; Lars Görmar; Maria H. González-Serrano; Ferran Calabuig (Journal of Innovation & Knowledge (JIK), 2022)
Coworking and its merits and benefits have been under heavy scholarly investigation. Also in practice, the phenomenon with its characteristics and manifestations becomes increasingly relevant on many levels and for many different types of people and organizations. But why is that so, and how are the research activities distributed between researchers, countries, and journals? To answer these questions, we first analyzed existing literature and extracted the focal points of the respective approaches. We conducted a cluster analysis on the existing literature by analyzing data from the Web of Science. With these clusters, we show the development of the research stream and how the studies are connected. The findings point towards the relevance of coworking spaces for innovative behavior and knowledge exchange, making them a place for work and social exchange and a tool for pursuing daily work, innovative ideas, knowledge creation, and interaction. With these findings, we contribute to the understanding of this research stream as a whole and provide a deeper understanding of the available studies and how they are connected. This allows researchers to understand where the interest came from, where it is going and how they can contribute to the topic. Our study indicates that scholars should take a broad approach towards the phenomenon coworking. It set food in many different research areas and all of them are important for a holistic understanding, showing potential for interesting studies. On a practical note, the factors that coworking influences need to be rethought throughout the whole work environment.
Keywords: M10; M13; M19; 650; Cluster analysis; Coworking; Innovation; Knowledge creation; Literature analysis